Assessing risk and adaptation for road infrastructure subject to natural and human hazards: a case study in the upper central sub-region of Thailand - Supitchayanat Sunawinworarat; Vilas Nitivattananon; Kampanart Silva; Pramanik, Malay; Santoso, Djoen San; Royal Thai Government (RTG) (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
This study assesses risk and effective adaptation measures for road infrastructure on Route 3196 in the Upper Central Sub-Region of Thailand. The study aims to identify key damage factors, assess risk and vulnerability, and determine appropriate adaptation measures. The scope includes analyzing factor and local hazard response capabilities and proposing adaptation measures to increase resilience, serving as a guideline for mitigation strategies. This research using the DPSIR and IPCC as a conceptual framework and collects both primary and secondary data. Primary data is obtained through surveys, expert interviews, and field observations, while secondary data is derived from official reports and GIS. Quantitative and qualitative methods such as MLRA and FGD are utilized to analyze the data and identify key damage factors and assess the resilience and vulnerability of road infrastructure. The study also proposes appropriate adaptation measures, analyzed using MCDA-AHP. The findings highlight the importance of factors such as vehicle weight, travel demand, and soil collapse in contributing to road damage. The study also reveals a high level of risk on Route 3196. Appropriately, the study proposes a range of adaptation measures, including road safety and support for geotechnical engineering, early warning systems, and water conservation measures. However, the study also identifies challenges and obstacles to the implementation of these measures, including limited funding and infrastructure. Therefore, the study underscores the importance of stakeholder collaboration and proactive management of adaptation measures to ensure the efficiency of road infrastructure in the face of natural and human hazards. Overall, this thesis provides a comprehensive understanding of road infrastructure problems caused and offers solutions to enhance the resilience of the road infrastructure. However, further analysis is required to expand the research scope, assess additional criteria, and evaluate the long-term effectiveness of the recommended measures. Addressing these areas can help make road infrastructure more resilient and mitigate the impact of hazards in similar contexts.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Urban Innovation and Sustainability
Thesis (M. Sc.) - Asian Institute of Technology, 2023
Keywords: Roads -- Risk management -- Thailand, Central; Roads -- Safety measures -- Thailand, Central